Land Management Options in Western Kenya and Eastern Uganda - Delve, Robert; Ramisch, Joshua (International Food Policy Research Institute, 2006)
In the recent past, the image of agricultural and environmental crises in Sub- Saharan Africa (SSA) has become increasingly common. Soil erosion and soil fertility loss are considered to be negatively affecting the productive capacity of the agricultural systems (Giller et al. 1997; Sanchez et al. 1997; Smaling, Nandwa, and Janssen 1997). These problems have been ascribed to many different causes: social (e.g., marginalization of the poor and women), political (e.g., structural adjustment programs), economic (e.g., poor availability and/or high prices of inputs, limited market opportunities), biological (e.g., increasing population and reducing land sizes), and physical (e.g., climatic change).